Ideal Cardiovascular Health and Incident Cardiovascular Disease Among Adults: A Systematic Review and Meta-Analysis - Garcia-Hermoso, A (Elsevier Ltd, 2018)
Objective: To investigate the association between ideal cardiovascular health (CVH) metrics and incident cardiovascular disease (CVD) by conducting a systematic review and meta-analysis of prospective cohort studies. Methods: The MEDLINE, EMBASE, and CINAHL databases were searched from January 1, 2010, through July 31, 2017, for studies that met the following criteria: (1) prospective studies conducted in adults, (2) with outcome data on CVD incidence and (3) a measure of ideal CVH metrics. Results: Twelve studies (210,443 adults) were included in this analysis. Compared with adults who met 0 to 2 of the ideal CVH metrics (high-risk individuals), a significantly lower hazard for CVD incidence was observed in those who had 3 to 4 points for the ideal CVH metrics (hazard ratio [HR]=0.53; 95% CI, 0.47-0.59) and 5 to 7 points (HR=0.28; 95% CI, 0.23-0.33). Weaker associations were observed in studies with older individuals, suggesting that there is a positive relationship between age and HR. Conclusion: Although meeting 5 to 7 metrics is associated with the lowest hazard for CVD incidence, meeting 3 to 4 metrics still offers an important protective effect for CVD. Therefore, a realistic goal in the general population in the short term could be to promote at least an intermediate ideal CVH profile (3 to 4 metrics). © 2018 Mayo Foundation for Medical Education and Research